Lagoon nurseries make a major contribution to adult populations of a highly prized coastal fish. (20th February 2017) - Tournois, Jennifer; Darnaude, Audrey M.; Ferraton, Franck; Aliaume, Catherine; Mercier, Lény; McKenzie, David J.
Abstract: This study investigated the contributions of five putative nursery areas, namely four coastal lagoons and the marine coastal zone, to the local offshore fishery of the gilthead sea bream Sparus aurata, in the Gulf of Lion (NW Mediterranean). A detailed database of multi‐elemental lagoon and marine otolith signatures was developed, based upon analysis of multiple sequential spots across growth bands of the otoliths of juveniles ( n = 142) sampled from the habitats over a 5‐yr interval. Adults of 10 annual cohorts ( n = 114), fished throughout the Gulf, were then submitted to a similar microchemical analysis of the growth band of their otoliths that was formed after nursery settlement in their first year. Using the juvenile signature database and Random Forest classification algorithms, adults were re‐assigned to the lagoons or marine coastal zone as a nursery. More than 80% of adults derived from lagoons, being ≥ 85.0% for five consecutive cohorts. Therefore, the marine coastal zone apparently contributed few adults, especially as a function of surface area. The four lagoons differed, however, in their contribution to the S. aurata fishery. Two lagoons qualified as "Effective Juvenile Habitats" that contributed more than 20% of the adults fished. Two shallow brackish lagoons were "Nursery‐Role Habitats" that contributed almost twice as many adults, per unit surface area, as the overall average. Such information can support strategies for sustainable management of multiple coastal lagoon habitats, and of valuable fisheries that depend upon them.